Alone against Hitler : Kurt von Schuschnigg's fight to save Austria from the Nazis - Bray, Jack 2020- (History, 2020)
"Alone Against Hitler tells the lesser-known but pivotal story of former Austrian Chancellor Kurt von Schuschnigg. As one of the first leaders to defy Adolf Hitler during the build-up to WWII, his is a story of lasting importance. Though young and untested upon entering office, von Schuschnigg courageously rejected the rising tide of Austrian Nazism, insisting on equal rights and respect for the Jewish minority. Author Jack Bray surveys the geopolitical conditions in Austria during the march to war, highlighting Von Schuschnigg's valiant four-year struggle to prevent his nearly defenseless small nation from being taken over from within by unrelenting, violent Austrian Nazis."--